Efficacy of Ergosterol and Ergosterol peroxide in different anti-inflammatory models – a comparison study - Luyao Li; Yuhang Zhu; Wenjing Cheng; Feiqian Di; Jiachan Zhang; Changtao Wang (Food and Agricultural Immunology)
Ergosterol and its peroxide with important regulatory roles in a variety of intracellular biological processes. In this study, both of the LPS- and UVA-induced human keratinocyte (HaCaT) inflammatory models were established to investigate the anti-inflammatory effects of ES and EP. The protective effects of EP and ES on UVA and LPS-induced cell damage were discussed by cell viability assays, reactive oxygen species levels, skin barrier-related proteins, anti-inflammatory factors, and expression of genes involved in related signaling pathways were analyzed. The results showed that both of ES and EP could reduce the intracellular ROS levels; inhibit IL-8 and IL-1β secretion; and had significant promotion effects on AQP3 and FLG, inhibited gene expressions of PI3K, AKt, IL-1β and IL-8 and ES and EP were not irritating according to the safety evaluation. In summary, both of ES and EP showed excellent anti-inflammatory effects and provided a degree of protection against UVA/LPS-induced inflammatory damage.